Current issues in age-related macular degeneration - Guymer, Robyn; Luu, Chi (Future Medicine Ltd, 2014)
This book brings together the history of our understanding of the disease and its treatments, and brings us to today, where we are on the cusp of major advances in the understanding of this devastating disease and its potential treatments.